A MALDI-Mass Spectrometry Imaging method applicable to different formalin-fixed paraffin-embedded human tissues. Issue 6 (19th June 2015) - De Sio, Gabriele; Smith, Andrew James; Galli, Manuel; Garancini, Mattia; Chinello, Clizia; Bono, Francesca; Pagni, Fabio; Magni, Fulvio
<x xml:space="preserve">Abstract</x> The paper shows a new method for the application of Matrix Assisted Laser Desorption/Ionisation (MALDI) Mass Spectrometry Imaging (MSI) technology on formalin-fixed paraffin-embedded (FFPE) tissue samples.